2013
DOI: 10.1007/s00213-013-3243-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic psychosocial stress causes delayed extinction and exacerbates reinstatement of ethanol-induced conditioned place preference in mice

Abstract: Rationale We have shown previously, using an animal model of voluntary ethanol intake and ethanol-conditioned place preference (EtOH-CPP), that exposure to chronic psychosocial stress induces increased ethanol intake and EtOH-CPP acquisition in mice. Objective Here, we examined the impact of chronic subordinate colony (CSC) exposure on EtOH-CPP extinction, as well as ethanol-induced reinstatement of CPP. Methods Mice were conditioned with saline or 1.5 g/kg ethanol and were tested in the EtOH-CPP model. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 73 publications
4
26
0
Order By: Relevance
“…No significant difference was found between the wild-type and M5 KO mice. These results indicate amphetamine-specific induction of anxiety-like behavior in the priming test in both genotypes of mice [42,43].…”
Section: Lower Dose Of Either Amphetamine or Morphine Priming Reinstasupporting
confidence: 56%
“…No significant difference was found between the wild-type and M5 KO mice. These results indicate amphetamine-specific induction of anxiety-like behavior in the priming test in both genotypes of mice [42,43].…”
Section: Lower Dose Of Either Amphetamine or Morphine Priming Reinstasupporting
confidence: 56%
“…As classical parameters related to anxiety behavior, the following parameters were hand-scored by the experimenter: i) the number of entries into the OA, ii) the time spent in the OA, and iii) the number of entries into the CA (overall activity). The maze was cleaned with 70% ethanol solution between tests [34,[40][41][42].…”
Section: Elevated-plus Maze (Epm) Testmentioning
confidence: 99%
“…After extinction, 0.8 g/kg of ethanol would reinstate the CPP induced by 1.6 g/kg. Reinstatement of CPP has also been demonstrated in C57Bl/6J mice [3], and they found that 0.5 g/kg of ethanol would markedly reinstate the CPP induced by 1.5 g/kg. But they used a unbiased CPP procedure with two chambers device and the training and testing time were different from us.…”
Section: Discussionmentioning
confidence: 90%
“…The place conditioning procedure was similar to that used previously to successfully produce CPP with ethanol [2,3,31] and processed in the following phases ( Fig. 1):…”
Section: Conditioned Place Preferencementioning
confidence: 99%